Is There Any Sectoral Cointegration in Indonesia Equity Market? - Surya, Aileen Clarissa; Natasha, Gabriella (International Research Journal of Business Studies, 2017)
An efficient portfolio, the one with low risk adjusted return, can be constructed using a good asset diversification. Sectoral diversification is one of the ways to reduce the portfolio risk since there are unique relationship among sector classifications. This research analyzes short and medium-run cointegration relationship among 9 sectoral indices in Indonesia equity market (JCI), using 2012-2016 weekly closing prices as the data. This study analyzed the relationship among these sectors using Johansen-Julius Cointegration Test and predict the causal relationship using Engle-Granger Causality and model the causalities using Vector Error Correction Model. Using empirical results of Johansen cointegration tests, this study finds that there is no cointegration in the short-run as the sector indices performance are caused by unique moving factors that affect all sectors differently. However, there is a medium run relationship among the sectors as they are moved by macroeconomic and political conditions towards the same direction. Other two methods, Engle-Granger and VECM, are also supporting the results from Johansen cointegration tests. The findings from this research can be useful as an insight for investors and fund managers in minimizing portfolio risk by using sectoral diversification, which based on the research can only be applied in the short run period.